2018
DOI: 10.1155/2018/8174345
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides: A Potential Neuroprotective Agent

Abstract: Ginseng is a traditional Chinese medicine with a wide range of pharmacological activities. Ginsenosides are the major constituents of ginseng. Ginsenosides have the unique biological activity and medicinal value, such as antitumor, anti-inflammatory, antioxidation, and inhibition of cell apoptosis. With the increase of stress in life, the incidence of nervous system diseases is also increasing. Neurological diseases pose a huge burden on people's life and health. In recent years, some studies have shown that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 79 publications
1
61
0
Order By: Relevance
“…It is controversial whether ginsenosides are permeable to the blood–brain barrier (Kang et al, ; H. J. Kim et al, ). But numerous studies have confirmed that systemic application of ginsenosides (intraperitoneal, subcutaneous, and oral) not only has antinoceciptive effect but also has anti‐inflammatory and neuroprotective effects in various neurological diseases (H. J. Kim et al, ; M. K. Kim et al, ; Mogil et al, ; Nemmani & Ramarao, ; Zheng et al, ), suggesting that ginsenosides have a regulatory effect on the central nervous system. But the mysteries behind this remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is controversial whether ginsenosides are permeable to the blood–brain barrier (Kang et al, ; H. J. Kim et al, ). But numerous studies have confirmed that systemic application of ginsenosides (intraperitoneal, subcutaneous, and oral) not only has antinoceciptive effect but also has anti‐inflammatory and neuroprotective effects in various neurological diseases (H. J. Kim et al, ; M. K. Kim et al, ; Mogil et al, ; Nemmani & Ramarao, ; Zheng et al, ), suggesting that ginsenosides have a regulatory effect on the central nervous system. But the mysteries behind this remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides are the major bioactive ingredients of ginseng mainly responsible for ginseng's beneficial effects (Zheng et al, ). Many studies in rodents suggest that ginsenosides have antioxidant and anti‐inflammatory properties and are effective to treat several neurodegenerative and metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, ginsenosides are considered to be major active ingredients of ginseng physiological activity, which have impacts on the nervous system, cardiovascular system, immune system and so on. 19 On the basis of different chemical structures of their aglycons, ginsenosides can be classified into three main types: protopanaxadiols (PPDs), protopanaxatriols (PPTs) and oleanolic acids. PPD-type includes ginsenosides Rb1, Rb2, Rc and Rd, while PPT-type includes ginsenosides Rg1, Rg2, Rf and Re.…”
Section: G In S Eng and Its Ac Tive Ing Red Ientsmentioning
confidence: 99%
“…It facilitates libido, mating performance and erectile dysfunction, and improves sperm quality and testosterone levels (Jang, Lee, Shin, Lee, & Ernst, ). Ginseng has been used to treat CNS diseases with positive outcomes (Zheng et al, ). A few studies examined the ameliorating effects of ginseng on epileptic patients and/or antiepileptic medications (Suleymanova, Gulyaev, & Chepurnova, ).…”
Section: Introductionmentioning
confidence: 99%